ANALISIS MARKETING SYARIAH PADA AIR MINERAL NU DRIZE - Ayu, Intan; 'Aini, Huril (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2023)
This research aims to analyze sharia marketing practices at Nu Drize in Lamongan. In this research the author designed a research design with a qualitative approach using an interview method with resource persons managing Nu Drize mineral water. The results of this research show that the implementation of Nu Drize marketing sharia includes the characteristics and principles of marketing sharia such as: (Teitis Rabbaniyah) prioritizing religious values, Ethical (Akhlaqiyah) maintaining behavior and service, Realistic (Al-Waqi-i'yyah) being professional and flexible, Humanistis (Insaniyyah) provides social assistance, Sharia Marketing Strategy which includes segmenting, targeting, positioning and Sharia Marketing Tactics which includes the 4P marketing mix. The implementation of Nu Drize marketing sharia values ​​is able to increase new outlets in every Fatayat branch in Lamongan and also to the general public of Lamongan.